Pendampingan Konselor Menangani Krisis Keluarga: Kasus Sonduk Hela di Suku Batak - Manullang, Priska; Sihombing, Sempurna; Halawa, Via Epiphanis; Sagala, Joyis (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
This research aims to be a provision or guide for counselors in accompanying the son-in-law experiencing a family crisis the sonduk hela case the Batak tribe. The focus of the research abaut in accompanying the son-in-law experiencing family crisis the sonduk hela case the Batak tribe in village of Pegagan Julu IV. This research used qualitative methods with literature research (library research), data collection through interviews, observation of data sources, documentation and data analysis using case studies. The results of the research are first by a cross-cultural approach, as a son-in-law becomes aware of the cultural rules Toba Batak, the heir is male and has the courage to make decisions, secondly by the Pastoral Case study metode approach, the son-in-law makes events that occur around him as objective or realistic inspiration, and aware of his identity when he is with his in-laws' family. Third, by cultural counselor approach (klb), pastoral case study method (mskp), and theological approach will help the son-in-law deal with the family crisis of the sonduk hela case the Batak tribe. Penelitian ini bertujuan menjadi bekal atau pegangan konselor dalam mendampingi menantu yang mengalami krisis keluarga kasus sonduk hela suku Batak. Fokus penelitian ialah menantu laki-laki yang mengalami krisis keluarga kasus sonduk hela suku Batak di desa Pegagan Julu IV. Penelitian ini menggunakan metode kualitatif dengan literature risearch (penelitian perpustakaan), pengumpulan data melalui Interview, Observasi sumber data, dokumentasi dan menganalisa data dengan Case study. Hasil penelitian ialah pertama melalui pendekatan lintas budaya, sebagai menantu laki-laki menjadi sadar dengan aturan budaya Batak Toba yaitu ahli waris adalah laki-laki dan berani menentukan keputusan, kedua melalui pendekatan Metode Studi Kasus Pastoral, menantu laki-laki menjadikan peristiwa yang terjadi disekitar sebagai inspirasi yang objektif atau realistis, serta menyadari jati dirinya saat bersama keluarga mertua. Ketiga, pendekatan konselor lintas budaya (klb), metode studi kasus pastoral (mskp), dan pendekatan teologi akan membatu menantu menangani krisis keluarga kasus sonduk hela di suku Batak.